Frequency of Electrolyte Imbalance and Hypertension in patients with Atrial Fibrillation - Muhammad Asad Raza, Ch. Adnan Ahmed Ather, Maria Nasir, Qamar Sajad, Saadia Ch, Hammad ur Rehman Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To determine the frequency of electrolyte imbalance and hypertension in patients with atrial fibrillation Method: A cross-sectional study was conducted on 163 patients in the Accident and Emergency department of Mayo Hospital Lahore from July 30, 2020 to January 30, 2021. Venous blood samples were taken from patients presenting with atrial fibrillation and sent to the Pathology department in Mayo Hospital to check for serum sodium and potassium levels. Patients were selected using non-probability consecutive sampling, with inclusion criteria of both genders of all ages, diagnosed with atrial fibrillation on the basis of electrocardiogram findings. Patients were excluded on the basis of patient’s history of prior use of anti-arrhythmic medications, congenital heart disease, valvular disease, chronic obstructive pulmonary disease or severe infections. Informed consent was taken from the patients after explanation of the study. Results: The study was conducted on a total of 163 patients of AF out of which 54 also had electrolyte abnormalities, and 22 were hypertensive. 15 of the patients with AF had coexisting hypertension and electrolyte imbalance (p value = 0.00001). Conclusion: The results show a high incidence of electrolyte imbalance and hypertension in patients of atrial fibrillation.